Implementasi Metode Six Sigma Pada Usaha UMKM Catering Di Desa Sendangrejo Kecamatan Ngimbang, Kabupaten Lamongan - Rochamah, Siti Nur Rochamah; Pristiana, Ulfi (Jurnal Akuntansi, Manajemen, Bisnis dan Teknologi, 2024)
Catering " Mbak Eka" is an MSME business engaged in grooming. Mbak eka catering always prioritizes the quality of its food products, but in the production process mbak eka catering experiences obstacles in product delivery and product defects. Late delivery in the form of delays in the delivery of catering orders to customers and for various defects there are shapes, tastes and colors that do not match customer orders. To overcome problems that occur in the MSME catering business, it can be done by identifying delays in order delivery and product defects, using the DMAIC six sigma method. DMAIC itself consists of define (formulate) using SIPOC diagrams (suppliers, inputs, processes, outputs, customers). Measure using DPMO calculations and control maps. Analyze using the results of interviews, observations and questionnaires for employees. Improve ( improve ) using 5 W+1H, interviews, observations and questionnaires for customers. Finally, there is control in this control using the results of observations, interviews and then SOPs will be made for catering businesses. From the results of the data, it is known that the chance of delay is 56.5%, so this study is more focused on delays in order delivery compared to defects. Keywords : Delivery Delay, Product Defect, Six Sigma, DMAIC